Strategy to emphasize the role of trees in the conservation and use of biodiversity - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
Scientists from ICRAF and Bioversity contributed to thematic studies on indicators of tree genetic diversity and livelihood benefits for the FAO State of the World's Forest Genetic Resources. The studies have contributed to the First FAO State of the World Forests Genetic Resources (SoW FGR) and the associated Global Plan of Action; and will contribute further to the Second SoW FGR in preparation for 2023.